Pengaruh Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Produk Dettol Hand Sanitizer Saat Pandemi COVID-19 - Sujana, Sujana; Adikarjo, Alvin Wijaya (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
The aims of this study were to analyze the effect of product quality on purchasing decisions of Dettol Hand Sanitizer, to analyze the influence of price on purchasing decisions of Dettol Hand Sanitizer and to analyze the effect of product quality and price simultaneously on purchasing decisions of Dettol Hand Sanitizer. The research method used is quantitative method with multiple linear regression analysis techniques. The population and sample used are Dettol Hand Sanitizer consumers in Bogor City. The results showed that partially both product quality and price had a positive and significant effect on purchasing decisions, therefore hypothesis 1 and hypothesis 2 are accepted. Furthermore, product quality and price simultaneously have a positive and significant effect on purchasing decisions and hypothesis 3 is accepted. Based on the results, it can be concluded that either partially or simultaneously, product quality and price significantly influence the purchasing decision of Dettol hand sanitizer. Keywords: Product Quality, Price, Purchase Decision.